2023
DOI: 10.2147/ijn.s401705
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Hydrogel Loaded with Chlorhexidine⊂β-CD-MSN Composites as Wound Dressing

Abstract: Background Much attention has been paid to sustained drug release and anti-infection in wound management. Hydrogels, which are biocompatible materials, are promising tools for controlled drug release and infective protection during wound healing. However, hydrogels also demonstrate limitations in the highly efficient treatment of wounds because of the diffusion rate. In this work, we explored pH-sensitive hydrogels that enable ultra-long-acting drug release and sustained antibacterial properties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…This prolonged release, lasting for 12 d, displayed substantial antibacterial action, principally attributed to the capability of β-CD to build an inclusion complex with CHX. In vivo tests further suggested that the hydrogels efficiently facilitated wound healing of skin and improved therapeutic effectiveness [228]. Do Nascimento et al in another study, aimed to develop and evaluate the healing characteristics of GelMA enriched with aqueous extract of Punica granatum, gallic acid (GA), or ellagic acid (EA) in a rodent model.…”
Section: Application Of Gelma In Wound Healingmentioning
confidence: 99%
“…This prolonged release, lasting for 12 d, displayed substantial antibacterial action, principally attributed to the capability of β-CD to build an inclusion complex with CHX. In vivo tests further suggested that the hydrogels efficiently facilitated wound healing of skin and improved therapeutic effectiveness [228]. Do Nascimento et al in another study, aimed to develop and evaluate the healing characteristics of GelMA enriched with aqueous extract of Punica granatum, gallic acid (GA), or ellagic acid (EA) in a rodent model.…”
Section: Application Of Gelma In Wound Healingmentioning
confidence: 99%
“…To control and prolong the release of drugs, HA was used as an NP coating, thus enhancing a stable and long-lasting repair effect on wound healing. Lin et al [82] described a new type of pH-sensitive wound dressing obtained by combining a hybrid gelatin methacrylate system with chlorhexidine-loaded silica NPs coated with HA. In vitro analysis demonstrated that this hydrogel provided an ultra-long-acting drug release with no cytotoxic effect on L929 fibroblast cells and a sustained antibacterial activity against S. aureus and E. coli.…”
Section: Nanomedical Applications Of Ha For Wound Healingmentioning
confidence: 99%
“…Their unique properties have positioned them as a significant focus of research and development as nanocarriers in drug delivery. [1][2][3][4][5][6][7][8][9][10][11][12] However, many studies have reported that slow biodegradability of MSNs could lead to severe particle bioaccumulation, potentially resulting in biosafety problems. [13][14][15][16] Generally, the degradation process of MSNs took several days, and the excretion of MSNs took several weeks from the body.…”
Section: Introductionmentioning
confidence: 99%